Optimization of Drill Geometry Design to Minimize Thermal Necrosis in Surgical Bone Drilling - Izamshah, R.; Noorazizi, M.S.; Kasim, M.S.; Hadzley, M.; Ali, M.A.; Sundi, S.A. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
During the orthopedic bone drilling surgery procedures, the friction between the drill and bones surface leads to a localized temperature increase results in thermal necrosis on the soft tissue surrounding the hole. The magnitudes of the friction energy are greatly dependent with the drill geometry design. Recognizing the importance on studying this phenomenon, this paper aim to investigate the effects of drill geometry on temperatures during the bone drilling procedure. Totals of 17 drills were design and tested with different geometry namely point angle, helix angle and web thickness on different penetration angle (0⁰, 15⁰, and 30⁰) to mimic the manually control penetration by the surgeon. From the conducted investigation, the most significant parameter that affects the temperature rise was the penetration angle followed by the point angle. In addition, the interaction between helix angle and web thickness also controlled the drilling temperature. From the result, the optimum drill-bit design geometry was 21.8% web thickness, 126.92° point angle and 36.53° helix angle which produces the minimum drilling temperature.